2018
DOI: 10.1161/jaha.118.009598
|View full text |Cite
|
Sign up to set email alerts
|

Primary Effect of SERCA2a Gene Transfer on Conduction Reserve in Chronic Myocardial Infarction

Abstract: Background SERCA2a gene transfer (GT) improves mechano‐electrical function in animal models of nonischemic heart failure Whether SERCA2a GT reverses pre‐established remodeling at an advanced stage of ischemic heart failure is unclear. We sought to uncover the electrophysiological effects of adeno‐associated virus serotype 1.SERCA2a GT following myocardial infarction (MI).Methods and ResultsPigs developed mechanical dysfunction 1 month after anterior MI, at which point they received intracoronary adeno‐associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
(40 reference statements)
1
17
0
Order By: Relevance
“…Based on these ndings, we surmised that there were no interactions between SERCA2a and Cx43 [8], and overexpression of neither of them solely could meet our goal. Guided by these ndings above, we applied two genes together after BMSCs transplantation.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Based on these ndings, we surmised that there were no interactions between SERCA2a and Cx43 [8], and overexpression of neither of them solely could meet our goal. Guided by these ndings above, we applied two genes together after BMSCs transplantation.…”
Section: Discussionmentioning
confidence: 90%
“…Also, data from qPCR (Fig. 1h) showed that gene-loading ratio reaches the maximum ((91.59±1.04% for S-Ad, 90.72±1.69% for C-Ad when adding 10 μl Ad (1×10p pfu/ml) to BMBs (100 μl, 1×10 9 /ml)), revealing that 1×10 8 BMBs could bind approximately 1×10 7 pfu of Ad. To determine both S-Ad and C-Ad loading capacity of BMBs (S/C-BMBs), both S-Ad and C-Ad were incubated with BMBs (100 μl, 1×10 9 bubbles/ml) at the ratio of 1:1 (10 μl : 10 μl), 1:2 (5 μl : 10 μl) or 2:1 (10 μl : 5 μl), respectively.…”
Section: Formation Of Ad-bmbs and Ad Loading Capacity Of Bmbsmentioning
confidence: 94%
See 1 more Smart Citation
“…The interpretation of these results is complicated by adaptive or maladaptive changes caused by constitutive genetic upregulation of SERCA obscuring primary consequences of combining RyR2 hyperactivity with enhanced SERCA2 function. Defining both direct and secondary consequences of SERCA2a stimulation against the backdrop of enhanced RyR2 activity is not only required for understanding the pathophysiology of Ca-dependent cardiac disease states but also has implications for the development and implementation of new therapies such as upregulation of SERCA2a in HF [19][20][21][22]. Therefore, to examine the primary effects of SERCA2 upregulation in the present study, we developed a mouse model that combines ablation of CASQ2 with doxycycline-inducible cardiac-specific overexpression of SERCA2a.…”
Section: Introductionmentioning
confidence: 99%
“…A hallmark of HF in both human and animal models is impaired Ca 2+ sequestration into the SR, which contributes to the decreased contractile performance in this disease (Gwathmey et al, 1987; Meyer et al, 1995; del Monte et al, 2002). Not surprisingly, this defective mechanism has been targeted with novel therapeutic strategies that are now undergoing experimental and clinical testing in animals and patients (Pfeffer et al, 2015; Hulot et al, 2016, 2017; Motloch et al, 2018). In this issue of JGP , provide novel insights into the molecular mechanism from which nitroxyl (HNO), nitric oxide (NO)’s one-electron-reduced and protonated sibling, recently emerged as a promising candidate for HF treatment.…”
mentioning
confidence: 99%